Perception of Heaviness Induced by Sensorimotor Incongruence Is Associated with Pain Prognosis: A Pilot Study - Soichiro Matsuda; Michihiro Osumi (Pain Research and Management)
Background. Patients with chronic musculoskeletal pain experience not only pain but also abnormal body perception. Such abnormal body perception has been reported to be caused by incongruence between motor intentions and sensory feedback (i.e., sensorimotor incongruence). However, the influence of abnormal body perception with sensorimotor incongruence on pain prognosis in musculoskeletal pain patients has not been investigated. Objective. We aimed at clarifying the influence of abnormal body perception on pain prognosis using an experimental procedure for inducing sensorimotor incongruence in patients with musculoskeletal pain. Methods. We recruited 18 patients within 2 months after limb fracture or ligament injury. In the experiment, patients sat with the intact upper or lower limb reflected in a large mirror aligned with the sagittal plane. A motor task was performed for 20 seconds in each of the congruent and incongruent conditions. In the congruent condition, patients were asked to perform flexion-extension movements with the intact and affected limbs in-phase, while observing the intact limb in the mirror. In the incongruent condition, patients were asked to perform flexion-extension movements antiphase, while observing the intact limb in the mirror. After performing the congruent and incongruent conditions, patients were asked to complete a questionnaire about abnormal body perception. These procedures were conducted within 2 months after the fracture (first), 2 weeks after the first measurement (second), and 4 weeks (third) after the first measurement. Results. Pain, heaviness, and peculiarity were more likely to be experienced in incongruent conditions. Additionally, structural equation modeling indicated that heaviness at the first time point predicted the pain intensity at the second and third time points. Conclusions. Heaviness caused by sensorimotor incongruence may predict pain prognosis in patients with musculoskeletal pain after one month.